EVALUASI DAERAH IRIGASI BENGAWAN JERO KABUPATEN LAMONGAN - Aris Setiawan; Nur Azizah Affandy (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Bengawan  Jero  Irrigation  Area  is  located  in  the  District  Administration  of  Work  Areas Karangbinangun, Lamongan.Objective of the research that for determine the level of damage that occurred  in  Bengawan  Jero  Irrigation  Area  and  determine  the  priority  scale  rehabilitation  of irrigation  area  of  Bengawan  Jero  damage.  Based  on  the  analysis  and  discussion,  analysis  of priority  rehabilitation  of  irrigation  area  of  Bengawan  Jero  using  Analytical  Hierarchy  Process (AHP) give first priority to sub-system 05 = 0.68. The next priority is a sub-system 07 = 0.44, subsystem 01 = 0.23, sub-system 09 = 0.70, sub-system 03 = 0.25, sub-system 10 = 0.42, sub-system 11 = 0.65 , sub-system 06 = 0.52, sub-system 08 = 0.54, sub-system 04 = 0.50 and last priority is the sub system  02 = 0.23. Selection of rehabilitation alternatives tailored to the available funds. If the available funds are insufficient for the rehabilitation of irrigation area Bengawan overall Jerothen rehabilitation can put emphasis on the primary channel only